Effects of cigarette smoking on HDL quantity and function: Implications for atherosclerosis - He, Bai-mei; Zhao, Shui-ping; Peng, Zhen-yu (Journal of cellular biochemistry, 2013)
ABSTRACT Cigarette smoking has been identified as an independent and preventable risk factor for atherosclerosis and cardiovascular disease. Population studies have shown that plasma high density lipoprotein (HDL) cholesterol levels are inversely related to the risk of developing cardiovascular disease. Cigarette smoking is associated with reduced HDL cholesterol levels. Cigarette smoking can alter the critical enzymes of lipid transport, lowering lecithin: cholesterol acyltransferase (LCAT) activity and altering cholesterol ester transfer protein (CETP) and hepatic lipase activity, which attributes to its impact on HDL metabolism and HDL subfractions distribution. In addition, HDL is susceptible to oxidative modifications by cigarette smoking, which makes HDL become dysfunctional and lose its atheroprotective properties in smokers. Therefore, cigarette smoking has a negative impact on both HDL quantity and function, which can explain, in part, the increased risk of cardiovascular disease in smokers. J. Cell. Biochem. 114: 2431–2436, 2013. © 2013 Wiley Periodicals, Inc.